Endophenotypic correlates of cognitive function in reproductive-age individuals with polycystic ovary syndrome - Heather G. Huddleston, M.D; Kaitlin B. Casaletto, Ph.D; Eleni G. Jaswa; Natalie L. Rasgon, M.D., Ph.D; Pauline P. Maki, PhD; Marcelle I. Cedars, MD; Lauri Pasch, PhD (Elsevier, 2022)
Objective: To characterize cognitive performance in relation to hormonal and metabolic factors in women with polycystic ovary syndrome (PCOS). Design: Cross-sectional study. Setting: Tertiary university center. Patient(s): A total of 48 individuals, aged 21-46 years, with PCOS according to the Rotterdam criteria. Intervention(s): Complete history and physical examinations, endovaginal ultrasounds, dermatologic assessments, neuropsychological assessments, and metabolic and hormonal serum tests. Main Outcome Measure(s): Sample-based z-scores on a comprehensive cognitive test battery. Result(s): Subjects were defined as having an androgenic (n = 31) or a nonandrogenic (n = 17) PCOS phenotype. Compared with their nonandrogenized counterparts, subjects with hyperandrogenism demonstrated lower relative performance on the tests of executive function (β-coefficient for the executive function composite z-score, −0.44; 95% confidence interval, −0.79 to −0.09), despite similar performance on the tests of memory, verbal reasoning, and perceptual reasoning. These differences were independent of age, years of education, and obesity. In an exploratory analysis in which subjects were stratified by the presence of insulin resistance (IR), subjects with PCOS with both IR and hyperandrogenism showed the lowest performance on a composite score of executive function, followed by those with hyperandrogenism alone. Conclusion(s): In this small study, subjects with hyperandrogenic PCOS demonstrated lower performance on the tests of executive function than subjects with nonandrogenic PCOS. Additional research is needed to confirm these findings in larger cohorts and investigate the role of modifiable factors, including IR, on cognitive outcomes.